Effect of high hydrostatic pressure extraction on biological activities and phenolics composition of winter savory leaf extracts - Moreira, Sílvia A. (2020)
Satureja montana L. has several biological properties related to its diverse composition of secondary metabolites. Nevertheless, it has been mainly studied for its essential oil, with only a few studies on the profile and bioactivities of the bioactive compounds from its leaf extracts being reported. This work aimed to study the antioxidant activity (by oxygen radical absorbance capacity (ORAC) assay), antimicrobial minimum inhibitory and bactericidal concentrations (MIC and MBC) determination, antibiofilm (by colorimetry), impact upon DNA (anti- and pro-oxidant assay), and cytotoxicity (by cell metabolism viability assays) of S. montana extracts obtained by high-pressure-assisted extraction (HPE). The extract obtained at 348 MPa, 35% (v/v) ethanol presented the highest concentration of individual phenolic compounds, and a minimum bactericidal concentration of 20 mg/mL against Listeria monocytogenes. HPE extracts showed antioxidant activity not only in ORAC but they were also able to prevent/attenuate peroxide-induced damage upon DNA. Moreover, on its own, HPE extract induced less oxidative damage than the control extract. Concerning the cytotoxicity, HPE extracts (at 0.5 and 1.0 mg/mL) were not harmful to HT29 cell lines, while control extracts (obtained at atmospheric pressure) at higher concentrations (>1.0 mg/mL) slightly reduced the metabolism of the cells. Finally, all extracts showed inhibition of the viability of 3 cancerous cell lines (>2.0 mg/mL for Caco-2, HeLa, and TR146) to below 15%.